IMPROVING CIRCULAR ECONOMY THROUGH TRAINING ON FINANCIAL DIGITALIZATION AND ECO-FRIENDLY PACKAGING: MENINGKATKAN EKONOMI SIRKULAR MELALUI PELATIHAN DIGITALISASI KEUANGAN DAN KEMASAN RAMAH LINGKUNGAN - Firmandani, Wahyu; Eriani, Izmi Dwira; Ervianty, Rizka Miladiah; Damayanti, Aurellia Nydia; Firdah, Diana Aulia; Nurul, Mochammad (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: MSMEs in Gresik Regency, particularly members of the Gresik Business Pioneer Community (KPUG), face challenges due to the continued use of manual financial records and non-environmentally friendly packaging, which limit access to financing and contribute to increased plastic waste. Objective: This community service initiative aimed to enhance the managerial capacity of MSMEs through financial digitalization and to promote the use of eco-friendly packaging as part of a green marketing strategy toward a smart and sustainable city. Method: The program was implemented in five stages: (1) socialization to raise awareness, (2) technical training based on partner needs, (3) application of technology through the use of automatic cash registers and biodegradable packaging, (4) continuous mentoring, and (5) evaluation using pre-tests, post-tests, and satisfaction surveys. Results: The program significantly improved participants’ competencies in digital financial management and the adoption of eco-friendly packaging. The average post-test score was 94, with all participants scoring above 80. Participant satisfaction averaged 4 out of 5. Conclusion: The activity effectively strengthened MSMEs’ managerial and marketing capacities, enhanced their access to financing opportunities, and supported circular economy practices aligned with environmental sustainability.